Seasonal and dietary effects on the hematobiochemical parameters of creole goats in the Peruvian Andes - Rodriguez Vargas, Anibal Raul; Sessarego Davila, Emmanuel Alexander; Castañeda Palomino, Katherine; Ormachea Sanchez, Huziel Héctor; Trillo Zarate, Fritz Carlos; Temoche Socola, Victor Alexander; Ruiz Chamorro, José Antonio; Cruz Luis, Juancarlos Alejandro (MDPI, 2025)
Creole goats have adapted to the harsh Andean environment, yet the physiological impacts of high-altitude production systems remain underexplored. This study assessed seasonal and dietary influences on the hematological and biochemical profiles of 45 Creole goats in the Peruvian Andes. The animals were assigned to three diets: D1 (grazing), D2 (grazing + 2000 g hay), and D3 (grazing + 400 g concentrate), across rainy and dry seasons. Biweekly blood sampling measured urea, cholesterol, total protein, albumin, ALP, ALT, WBCL, NeuP, LymP, HGB, and MCV. Season exerted the strongest influence (p < 0.001), with modest dietary effects and a consistent effect of sampling time. Urea, total protein, and albumin increased during the rainy season, though only urea responded significantly to diet. Leukocytosis rose in the dry season and with higher-protein diets, suggesting heightened immune activation under environmental stress. Hemoglobin peaked in the rainy season and early sampling, indicating better oxygenation. MCV and body weight were higher in the dry season, with weight unaffected by diet. These results underscore the complex interplay of environmental and nutritional factors in shaping goat physiology at high altitudes, emphasizing the importance of dynamic modeling in sustainable Andean livestock systems.